When Things Go Wrong In Urology Reflections to Improve Practice - Motiwala, Faiz.; Motiwala, Hanif; Goonewardene, Sanchia S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides a guide on how to navigate and avoid medico-legal problems associated with the management of patients with urological diagnosis. Each chapter focuses on a different medical situation related to urology and discusses how they can be managed. The book aims to utilise the experience and understanding of its authors to help its readers manage and avoid medico-legal issues. This book is relevant to urologists, allied health professionals, nurses, physiotherapists, physicians, and medical legal practitioners.
1. Medico-legal pitfalls -- 2. Communication -- 3. Equipment problems -- 4. Prescribing -- 5. Diagnostics -- 6. Managing patient expectations -- 7. Administrative complications -- 8. Theatre issues -- 9. Staff training -- 10. Human factors in healthcare -- 11. Access to healthcare -- 12. NHS culture -- 13. Raising concerns and problems in training -- 14. Managing a complaint -- 15. Managing an GMC investigation -- 16. Medical indemnity.
Keywords: Urology; Surgery; Urology; Surgery; Urologic Diseases